2006
DOI: 10.1038/sj.ki.5001533
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous immune response modulates the course of IgA-immune complex mediated nephropathy

Abstract: In animal models of IgA nephropathy, the inevitable endogenous immune response to passively administered antigens alone or in complex with specific IgA mask the exact role each might play in pathogenesis. To delineate the role the immune response might play, we have developed a passive model with exclusive IgA-immune complex-mediated nephropathy in B-cell-deficient (BCD) mice. Glomerular IgA immune deposits were induced by administration of purified IgA antiphosphorylcholine and the specific pneumococcal C-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
(46 reference statements)
0
30
0
Order By: Relevance
“…We show here that exposure of mesangial cells to oxidised and even native LDL in small amounts, such as might occur in vivo, can potently stimulate IL6 production. IL6 may contribute to the pathogenesis of glomerular injury either by modulation of the immune system [29] or by directly promoting glomerular damage [30]. We also found that glycated LDL particles are more potent than oxidised LDL in enhancing IL6 levels, with a more prolonged effect (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…We show here that exposure of mesangial cells to oxidised and even native LDL in small amounts, such as might occur in vivo, can potently stimulate IL6 production. IL6 may contribute to the pathogenesis of glomerular injury either by modulation of the immune system [29] or by directly promoting glomerular damage [30]. We also found that glycated LDL particles are more potent than oxidised LDL in enhancing IL6 levels, with a more prolonged effect (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we decided to use the IgAN model passively induced by repeated injections of IgA and PnC antigen so that it was more feasible in performing the induction of the experimental IgAN in NLRP3 KO mice, and also because it was indeed a very stable IgAN model to reproduce the characteristic granular immunofluorescence pattern of IgA and C3 mesangial deposits, with renal inflammation and fibrosis720214243 and has been used in various experiments involving [1] the role of different IgA subtypes in IgA ICs glomerular deposition, [2] complement activation and ICs deposition, [3] the clearance kinetics of circulating IgA ICs and the role of hepatic Kupffer cells in their elimination, [4] the impact of the nature of antigen in IgA ICs in resultant renal injury, and [5] the synergy between extra-renal cytokines and IgA mesangial deposits in the development of renal injury and dysfunction and in the evolution of renal histopathologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…IgAN was induced by daily injection of purified IgA anti-phosphorylcholine and pneumococcal C-polysaccharide (PnC)27, and all animal experiments were performed with the approval (permit number IACUC-11-063) by the institutional animal care and use Committee of the national defense medical center, Taiwan. The tissues were fixed in 10% buffered formalin and embedded in paraffin, and serial sections (4  μ m) were cut using Leica RM2155 and stained with hematoxylin and eosin (H&E).…”
Section: Resultsmentioning
confidence: 99%